The Development Process of Awang Sains 2D Digital Mobile Game - Mohd Radhi Md Shukri; Shamsul Arrieya Ariffin (Pejabat Karang Mengarang UPSI, 2019)
This article presents the process of the development of a 2D digital mobile game; Awang Sains. The game has been developed based on features that have been identified, and will be tested for its heuristics - usability, mobility, playability, learning content, local content, language and aesthetics. Fifteen experts were selected to play and then test and evaluate the game. The objective of this game is to use it in teaching and learning Science year 4. The study used design and develop research (DDR) embedded with the ADDIE model (analysis, design, develop, implement, and evaluate), based on pedagogy and the instructional need to make the software meaningful with the ability to help pupils master Science subjects.